CATHETER ABLATION OF VENTRICULAR TACHYCARDIA - LONG-TERM RESULTS - Fiala, Martin; Heinc, Petr; Lukl, Jan (Biomedical papers, 2000)
Ventricular tachycardia represents life-threatening cardiac rhythm disturbance and catheter ablation usingradiofrequency current provides powerful means for definitive cure of almost all monomorphic tachyarrhythmias.Presence and extent of underlying structural heart disease is important for further prognosis of the patients, whoundergo catheter ablation of ventricular tachycardia. Long-term results of catheter ablation for ventriculartachycarida in patients with and without structural heart disease are presented.Patients and results: Twenty three patients (9 females) aged 49.1 extpm 15.6 (18-72) years underwent catheterablation for monomorphic (resp. polymorphic in one patient) ventricular tqachycardia in 30 ablation procedures.Patients with structural heart disease: Seven patients (2 females) aged 54.2 extpm 19.8 (21-72) years had structural heartdisease (5 patients - post myocardial infarction, 1 patient - arrhythmogenic right ventricular dysplasia, 1 patient- surgically corrected transposition of great arteries). All sustained monomorphic ventricular tachycardias wereeliminated during the catheter ablation and no ventricular tachycardia recurred during the follow-up period in 4patients. In two patients sustained monomorphic ventricular tachycardia was not eliminated with radiofrequencycurrent. One of the patients remains free of ventricular tachycardia and one patient experienced one recurrence ofslowed ventricular tachycardia. Thus long-term clinical success was achieved in 4 patients and some clinical benefitprobably also in the latter two patients. A different ablation strategy targeting large arrhythmogenic area at theborder of postmyocardial infarction scar was employed in the last patient with frequent ICD discharges forpolymorphic ventricular tachycardia associated with hemodynamic deterioration. This procedure brought immediateand long-term significant reduction of ICD shocks and rehospitalizations and probably was life-saving. Patientswithout structural heart disease: In sixteen patients (7 females) aged 44.2 extpm 12.8 (18-66) years no structural heartdisease was found. These patients presented with documented ventricular ectopy in different forms from incessantventricular premature beats through repetitive nonsustained ventricular tachycardia to paroxysmal sustainedventricular tachycardia. The arrhythmia originated in the right ventricle in 11 patients (right ventricular outflowtract in 10 patients and basolateral wall in 1 patient) and in the left ventricle in 5 patients (inferoapicoseptal regionin 4 patients and basoinferoseptal region in 1 patient). Eleven patients (68.7 %) had the arrhythmia eliminated ormarkedly suppressed during the ablation procedure and remain free of palpitations and antiarrhythmic drugs. Twopatients with partial suppression of the ectopic rhythm are less symptomatic and the antiarrhythmic drugs could bereduced. In one patient one ventricular tachycardia morphology from the right ventricular outflow tract waseliminated while the second ventricular tachycardia morphology was not targeted (and was suppressed byantiarrhythmic drug) for close vicinity of the arrhythmogenic focus to the left anterior descending artery. Thus theclinical benefit of the ablation procedure is enhanced to 14 (87.5 %) patients. Ablation completely failed in twopatients.Conclusion: Radiofrequency catheter ablation of ventricular tachycardia is highly effective and safe and resultsin long-term arrhythmia elimination. In patients with underlying structural heart disease it should be currentlyviewed as a adjunctive therapy to a complex management of the patient, while in otherwise healthy patients it can beconsidered a method for permanent cure.
Keywords: Ventricular tachycardia / Radiofrequency catheter ablation